Apolipoprotein specificity of the chicken oocyte receptor for low and very low density lipoproteins: lack of recognition of apolipoprotein VLDL-II. - J Nimpf; R George; W J Schneider (Journal of Lipid Research, 1988)
At onset of egg-laying in the chicken, plasma levels of apolipoprotein VLDL-II (apoII) increase dramatically, suggesting a function of apoII in yolk deposition of triglyceride-rich lipoproteins. Thus, the possibility that this female-specific homodimeric protein (Mr of subunit, 9500) is recognized by the oocyte receptor for low and very low density lipoproteins was investigated. ApoII was purified from very low density lipoproteins by a novel, rapid procedure and reconstituted with egg phosphatidylcholine (PC) by detergent-dialysis. The resulting discoidal apoII/PC lipoprotein particles contained 3 mg of apoII per mg of PC and had a buoyant density of 1.062 g/ml. The ability of apoII/PC, as well as of physiological particles containing apoII but devoid of apolipoprotein B (apoB), namely high density lipoproteins (HDL) from laying hens, to interact with the oocyte receptor was tested. Both of these ligands failed to show saturable high affinity binding, in contrast to the apoB-containing ligands, low and very low density lipoproteins. Furthermore, neither laying-hen HDL which contain apoII and apoA-I nor apoII/PC were able to displace receptor-bound apoB-containing lipoproteins, as shown in competitive binding assays as well as by ligand blotting. Thus, we conclude that apoB, but not apoII, participates in binding and uptake of very low density lipoproteins via receptor-mediated endocytosis by growing chicken oocytes.